Fibroadenoma of Ectopic Mammary Tissue in the Vulva ? A Case Report - Maha M. Arafah; Shaesta N. Zaidi (Journal of King Abdulaziz University: Medical Sciences, 2023)
Aberrant breast tissue can occur anywhere along the embryonic mammary streak. Its presence in the vulva is an uncommon clinical or pathological finding. The ectopic breast tissue can be the site of the same physiological or pathological process found in the normal breast. The developing of fibroadenoma is a rare entity and has rarely been reported in the literature. A case report of 46-years-old female was presented with an unknown progressively increasing mass in the vulva. Excision of the mass was performed, which on histology, it demonstrated the fibroadenoma with mammary tissue surrounding it, and with positive hormone receptors.